(untitled) - Atwood, Margaret (Cambridge, U.K., 2002)
This book grew out of the series of Empsom lectures that prize-winning novelist Atwood gave at the University of Cambridge in 2000. In it, she addresses a number of fundamental questions: not how to write but the basic position of the writer, why a writer writes, "and for whom? And what is this writing anyway?" Wearing her learning lightly, Atwood allows her wit to shine on almost every page. Following an initial autobiographical chapter, Atwood addresses major issues: the duplicity evidently inherent in writing; the problems of art vs. money; the problems of art vs. social relevance; the nature of the triangular relationship of writer, reader, and book; and, in the final title chapter, the provocative idea that "all writing of the narrative kind, and perhaps all writing, is motivated, deep down, by a fear of and a fascination with mortality by a desire to make the risky trip to the Underworld, and to bring something or someone back from the dead." Atwood is not looking to provide answers or solutions but to explore the parameters of some interesting questions.
Keywords: Fiction,Tiểu thuyết, Authorship,Nghề Viết Văn; Authorship,Nghề viết văn